THE POTENTIAL FOR DEVELOPMENT OF DIANA WATERPARK AS A TOURISM OBJECT IN BALUSU VILLAGE, BALUSU DISTRICT, BARRU DISTRICT - Mahmud, Usamah; Marsuki; Mirnawati (P3M Stia Al Gazali Barru and Meraja media, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal